CC-VIT: Virtualization Intrusion Tolerance Based on Cloud Computing - Yuesheng Tan; Dengliang Luo; Jingyu Wang (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
Service integration and supply on-demand coming from cloud computing can significantly improve the utilization of computing resources, reduce power consumption of per service, and effectively avoid the error of computing resources. However, cloud computing is still facing the problem of intrusion tolerance of the cloud computing platform and sensitive data of new enterprise data center. In order to address the problem of intrusion tolerance of cloud computing platform, this paper constructs a virtualization intrusion tolerance system based on cloud computing by researching on the existing virtualization technology. This system adopts the method of hybrid fault model, active and passive replicas, state update and transfer, proactive recovery and diversity, and initially implements to tolerate F faulty replicas in N =2F+1 replicas and ensure that only F+1 active replicas to execute during the intrusion-free stage. The remaining replicas are all put into passive mode, which significantly reduces the resource consuming in cloud platform.